External strengthening of unreinforced masonry walls with polymers reinforced with carbon fiber (2018)
In many countries, buildings are usually made of unreinforced clay masonry walls, especially in Colombia. These constructions have low resistance and ductility, and are very vulnerable to seismic events, due to their low capacity of energy dissipation. This paper reports the results obtained from a research project that evaluates the behavior of reinforced masonry walls under lateral loads. The reinforcement was made using Carbon Fiber Reinforced Polymers (CFRP). In the test program, eight (8) clay masonry walls were built using hollow brick. Four (4) of them were 1,23 m long and 1,90 m high and the remaining four (4) were 2,47 m long and 1,90 m high. Four (4) walls were tested with a static lateral load and four (4) with a cyclic lateral load in its plane. Results revealed that the presence of the reinforcement material significantly increased the ultimate load and deformation capacity, provided that the material has a suitable anchoring system.